2014
DOI: 10.1063/1.4873760
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the process parameters on the replication of microstructured freeform surfaces

Abstract: -Surfaces of technical parts are getting more and more attention in terms of functionalization. By modification, additional functionality is given to the part, e.g. self-cleaning effect or antireflection behavior. Nowadays mainly flat surfaces are structured which is a consequence of the available production methods. However, the demand of micro structured free form surfaces is increasing, enabling novel products. A major problem in the mass production (e.g. injection molding) of structured freeform surfaces i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The surface topography of study samples is measured using Zygo's Nexview 9000 4 coherence scanning interferometer (CSI) with 10X objective and 0.95 μm lateral resolution. The mould tool surfaces are replicated using Technovit ® Provil Black polyvinyl siloxanes 5 material.…”
Section: Surface Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface topography of study samples is measured using Zygo's Nexview 9000 4 coherence scanning interferometer (CSI) with 10X objective and 0.95 μm lateral resolution. The mould tool surfaces are replicated using Technovit ® Provil Black polyvinyl siloxanes 5 material.…”
Section: Surface Characterizationmentioning
confidence: 99%
“…The surface texture on the components is a replication of the grain pattern in the mold cavity, and to avoid variations in color and gloss it is important to have good replication of the grain pattern. Unfortunately, a large number of material and processing parameters affects the replication and a substantial number of investigations have therefore been carried out to improve the knowledge about robust injection moulding of textured components with high-aspect ratio [1][2][3][4][5][6][7][8]. In this study, the effect of texture, tool temperature, holding pressure and injection speed on surface texture replication of injection moulded PC-ABS (Polycarbonate-Acrylonitrile butadiene Styrene) samples and its relationship with measured gloss are investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The replication of nanostructures in the nanoimprint process is commonly limited to draft angles equal or smaller than 90°, but recently it was also shown that undercut structures as well as nano-cavities could be replicated when the right materials for the stamp and imprint material are chosen [ 11 , 29 ]. The process parameters of the replication—especially of the demolding step—are critical for freeform microstructures [ 30 ]. Also, innovative alternatives such as shape memory polymers have been reported [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%